Privatization under Asymmetric Information - Dieter Bös (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper models privatization as a cooperative game between the government, a trade union and the private shareholders. These players kno w that privatization increases the efficiency of a firm, but only the management of the firm knows the exact value of the relevant productivity-increasing parameter. This incomplete information changes many of the results which were attained in Bös (1991) in a full-information setting.
Keywords: 330; Privatization; asymmetric information